1.2% Rosuvastatin Versus 1.2% Atorvastatin Gel Local Drug Delivery and Redelivery in Treatment of Intrabony Defects in Chronic Periodontitis: A Randomized Placebo‐Controlled Clinical Trial. Issue 7 (1st July 2016) - Pradeep, A.R.; Garg, Vibhuti; Kanoriya, Dharmendra; Singhal, Sandeep
Abstract : Background: Statins (3‐hydroxy‐3‐methylglutaryl coenzyme A reductase inhibitors) are an important group of hypolipidemic drugs that are able to modulate inflammation and alveolar bone loss. Rosuvastatin (RSV) and atorvastatin (ATV) are known to inhibit osteoclastic bone resorption and have been proposed to have osteostimulative properties. The aim of this study is to evaluate and compare the efficacy of 1.2% RSV and 1.2% ATV gel local drug delivery (LDD) and redelivery systems, in addition to scaling and root planing (SRP), for the treatment of intrabony defects (IBDs) in patients with chronic periodontitis (CP). Methods: A total of 90 individuals with 90 IBDs was randomly allocated to treatment with SRP followed by LDD of 1.2% RSV, 1.2% ATV, or placebo gel. Clinical and radiographic parameters, including plaque index (PI), modified sulcus bleeding index (mSBI), probing depth (PD), clinical attachment level (CAL), and IBD depth, were recorded at baseline and 6 and 9 months. Results: All three groups showed significant reduction in PI and mSBI at all intervals. Mean mSBI and PD reductions, CAL gain, and IBD depth reduction with statin drugs were significantly greater than with placebo gel LDD. Improvements in these parameters were significantly greater with RSV LDD than ATV or placebo gels at 6 and 9 months. Conclusion: LDD of 1.2% RSV results in significantly greater clinico‐radiographic improvement than 1.2% ATV or placebo gels as adjunct to mechanical periodontal therapy.